Biovillage worldwide: building on multifunctionality of vermicompost technology - B. Bhattacharya; S.K. Nanda (Journal of Agricultural Extension Management, 2025)
Biovillages are emerging as composite eco-technology packages for achieving the UN Millennium Development Goals of reducing poverty, eliminating hunger and sustaining life-support systems of this planet. As part of an evolving forum, Biovillage Worldwide, we have been exploring with colleagues the niche between the technological and institutional horizons of biovillages. We believe that the future of agriculture and rural development will be shaped by the creative utilization of biological inputs, biological agents, biological processes and ecological knowledge. We share here our understanding and reflections on how current experiences of disseminating vermicompost technology can be harnessed for building bio villages across rural Asia